Digital Leadership as the Key to Service Transformation in Public Sector Organizations - Rudi Salam; Jamaluddin; Denok Sunarsi; Daswati; Syahruddin Hattab (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2026)
The rapid development of digital technology requires public sector organizations to transform their services to become more efficient, transparent, and citizen-oriented. This study aims to analyze the role of digital leadership in driving service transformation within public sector organizations in Indonesia. The research employs a qualitative descriptive approach, with data collected through in-depth interviews, observations, and document analysis involving selected informants using purposive sampling. The findings reveal that digital leadership significantly influences service transformation through the development of a clear digital vision, the strengthening of organizational culture and human resource capabilities, and the promotion of innovation in service delivery, leading to improved efficiency, accessibility, and transparency of public services. However, this study is limited by its qualitative design with a relatively small number of informants, its focus on leadership perspectives, and the lack of in-depth analysis of regional disparities in infrastructure. Future research is recommended to use quantitative or mixed methods, incorporate citizen perspectives, and explore the role of emerging technologies such as artificial intelligence and big data in enhancing digital leadership and public service innovation.